INTERVENSI KYAI DALAM RESTRUKTURISASI BIROKRASI DI KABUPATEN SITUBONDO - Giyanto Giyanto (CERMIN: Jurnal Penelitian, 2018)
Bureaucracy reform programs are structured as a step to overcome the fundamental problems that occur in the implementation of government both central and local government. This study aims to analyze the extent ofKyai's intervention in the framework of bureaucratic reform in Situbondo regency. This research uses descriptive explanative research method. The results of this study indicate that kyai intervention has great power in reforming government bureaucracy in Situbondo.